An Unexpected Cause of Severe Hypokalemia - Fernando Caravaca-Fontan; Olga Martinez-Saez; Maria Delgado-Yague; Estefania Yerovi; Fernando Liaño (Case Reports in Nephrology)
We describe an unusual case of severe hypokalemia with electrocardiographic changes, due to licorice consumption, in a 15-year-old female student with no previous medical history. Prompt replacement of potassium and cessation of licorice ingestion resulted in a favourable outcome. We also discuss the pathophysiology and diagnosis, emphasizing the importance of a detailed anamnesis to rule out an often forgotten cause of hypokalemia as the licorice poisoning.